Control of Temperature and Aluminum Fluoride Concentration Based on Model Prediction in Aluminum Electrolysis - Zeng Shuiping; Wang Shasha; Qu Yaxing (Advances in Materials Science and Engineering)
The temperature and the aluminum fluoride (AlF3) concentration of electrolyte greatly affect the current efficiency and energy consumption in aluminum electrolysis. This paper developed a new kind of algorithm to control the temperature and AlF3 concentration of electrolyte for 300 kA prebake aluminum production cells by altering the setting cell voltage and the AlF3 adding rate. One is liquidus model which can be used to calculate AlF3 concentration of electrolyte by some technical parameters and target superheat and the other is the temperature models which can determine the required cell voltage by the technical parameters and target temperature. Consequently, the AlF3 addition rate can be decided by the AlF3 concentration. The temperature and AlF3 concentration of electrolyte in the production are measured and the differences between the measurement and the corresponding calculation are used as feedback to correct the model. The coefficients in the model are also revised according to the external conditions. This system has been used in an aluminum company for 2 years. Both the temperature and the AlF3 concentration of electrolyte can be controlled as required and the energy consumption of the aluminum production was much decreased.